YAG:Ce3+@ beta-SiALON 형광체를 이용한 InGaN 광전극의 효과적인 물분해 - 배효정(Hyojung Bae); 이대장(Daejang Lee); 차안나(An-Na Cha); 주진우(Jin-Woo Ju); 문영부(Youngboo Moon); 하준석(Jun-Seok Ha) (Current Photovoltaic Research, 2020)
GaN based photoelectrode has shown good potential owing to its better chemical stability and tunable bandgap with materials such as InN and AlN. Tunable bandgap allows GaN to make the maximum utilization of solar spectrum, which could improve photoelectrode performance. However, the problems about low photoelectrode performance and photo-corrosion still remain. In this study, we attempt to investigate the photoelectrochemical (PEC) properties of phosphor application to InGaN photoelectrode. Experimental result shows YAG:Ce3+ and beta-SiALON phosphor result in the highest photoelectrode performance of InGaN. KCI Citation Count: 0